2015
DOI: 10.1007/s00109-015-1264-4
|View full text |Cite
|
Sign up to set email alerts
|

Kidney injury is independent of endothelial HIF-1α

Abstract: HIF-1α controls hypoxic survival and adhesion on endothelial cells (EC) in vitro. In vivo, HIF-1α expression in renal EC is low. Deletion of HIF-1α in EC does not affect kidney development and function in mice. Renal function after acute and chronic kidney injury is independent of HIF-1α in EC. Data suggest organ-specific regulation of HIF-1α function in EC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
1
10
1
Order By: Relevance
“…We and others have previously identified endothelial HIF-2 as the key transcription factor regulating postischemic kidney injury under PHD2-competent conditions, 14,44 whereas endothelial HIF-1 was dispensable. 14,45 Although these observations appear to contrast with this study, we believe that these are not conflicting findings. Our findings reveal that endothelial PHD2 deficiency reverses the susceptibility to AKI due to endothelial HIF-2 loss, 14 a response that involves endothelial HIF-1 signaling derived from an extrarenal vascular bed.…”
Section: Cre-ec-phd2 Hif2contrasting
confidence: 95%
“…We and others have previously identified endothelial HIF-2 as the key transcription factor regulating postischemic kidney injury under PHD2-competent conditions, 14,44 whereas endothelial HIF-1 was dispensable. 14,45 Although these observations appear to contrast with this study, we believe that these are not conflicting findings. Our findings reveal that endothelial PHD2 deficiency reverses the susceptibility to AKI due to endothelial HIF-2 loss, 14 a response that involves endothelial HIF-1 signaling derived from an extrarenal vascular bed.…”
Section: Cre-ec-phd2 Hif2contrasting
confidence: 95%
“…Kalucka et al have observed that HIF‐1α does not affect renal development, renal vascular architecture, or renal function in endothelial cells and therefore is not related to CKD both in vivo (mice) and in vitro (endothelial cells). The only relationship of HIF‐1α in endothelial cells is to the survival in hypoxia and leukocyte adhesion, without any real link to the development of renal diseases.…”
Section: Discussionsupporting
confidence: 89%
“…Another revealed factor was that NF‐κB contributes to the activation of Ang 2 and that the combination of HIF‐1α and NF‐κB function as an advanced signalling cycle, persisting in raising the levels of both genes; this leads to the progression of hypertension, a number of endothelial vasoactive factors, and, consequently, CKD aggravating towards ESRD. In contrast to all the studies performed, Flisinski et al and Kalucka et al observed that HIF‐1α does not affect renal development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kalucka J et al found that loss of HIF-1α in glomerular endothelial cells increases hypoxic cell death in vitro, but in vivo, HIF-1α expression in endothelial cells in mouse kidneys is detectable but limited. As a result, endothelial cell-specific ablation of HIF-1α does not have obvious effects on developmental phenotype in the kidney and also no influence of renal function and adhesion molecules expression during fibrosis development after UUO [ 49 , 53 ]. Kapitsinou P et al further showed that inhibition of total endothelial HIF can aggravate renal fibrosis significantly in both ischemia-reperfusion and ureteral obstruction models.…”
Section: Hif In Chronic Kidney Disease (Ckd)-associated Renal Fibrmentioning
confidence: 99%
“…However, in vivo work indicates that HIF-1α expression in endothelial cells in mouse kidneys is detectable but limited. Therefore, endothelial cell-specific ablation of HIF-1α has no effect on kidney development and no influence on renal function and adhesion molecules expression during inflammation after UUO [ 53 ]. The limited role of endothelial HIF-1 in inflammation is also confirmed in another study [ 49 ].…”
Section: Hif In Ckd-associated Syndromesmentioning
confidence: 99%